Disruption of Early Tumor Necrosis Factor Alpha Signaling Prevents Classical Activation of Dendritic Cells in Lung-Associated Lymph Nodes and Development of Protective Immunity against Cryptococcal Infection - Jintao Xu (American Society for Microbiology, 2016)
ABSTRACT Anti-tumor necrosis factor alpha (anti-TNF-α) therapies have been increasingly used to treat inflammatory diseases and are associated with increased risk of invasive fungal infections, including Cryptococcus neoformans infection. Using a mouse model of cryptococcal infection, we investigated the mechanism by which disruption of early TNF-α signaling results in the development of nonprotective immunity against C. neoformans. We found that transient depletion of TNF-α inhibited pulmonary fungal clearance and enhanced extrapulmonary dissemination of C. neoformans during the adaptive phase of the immune response. Higher fungal burdens in TNF-α-depleted mice were accompanied by markedly impaired Th1 and Th17 responses in the infected lungs. Furthermore, early TNF-α depletion also resulted in disrupted transcriptional initiation of the Th17 polarization program and subsequent upregulation of Th1 genes in CD4+ T cells in the lung-associated lymph nodes (LALN) of C. neoformans-infected mice. These defects in LALN T cell responses were preceded by a dramatic shift from a classical toward an alternative activation of dendritic cells (DC) in the LALN of TNF-α-depleted mice. Taken together, our results indicate that early TNF-α signaling is required for optimal DC activation, and the initial Th17 response followed by Th1 transcriptional prepolarization of T cells in the LALN, which further drives the development of protective immunity against cryptococcal infection in the lungs. Thus, administration of anti-TNF-α may introduce a particularly greater risk for newly acquired fungal infections that require generation of protective Th1/Th17 responses for their containment and clearance. IMPORTANCE Increased susceptibility to invasive fungal infections in patients on anti-TNF-α therapies underlines the need for understanding the cellular effects of TNF-α signaling in promoting protective immunity to fungal pathogens. Here, we demonstrate that early TNF-α signaling is required for classical activation and accumulation of DC in LALN of C. neoformans-infected mice. Subsequent transcriptional initiation of Th17 followed by Th1 programming in LALN results in pulmonary accumulation of gamma interferon- and interleukin-17A-producing T cells and effective fungal clearance. All of these crucial steps are severely impaired in mice that undergo anti-TNF-α treatment, consistent with their inability to clear C. neoformans. This study identified critical interactions between cells of the innate immune system (DC), the emerging T cell responses, and cytokine networks with a central role for TNF-α which orchestrate the development of the immune protection against cryptococcal infection. This information will be important in aiding development and understanding the potential side effects of immunotherapies.